Isolation and localization of herpes simplex virus type 1 mRNA. - Anderson, K P (1979)
Herpes simplex virus (HSV) DNA bound to cellulose has been used as a reagent to isolate viral mRNA for size analysis on denaturing agarose gels. Total viral polysomal polyadenylated RNA was isolated from cells late after infection when such RNA has sequences encoded by approximately 45% of the HSV DNA. This RNA has a size range of from 1.5 to greater than or equal to 8 kilobases, with certain sizes, such as 1.7 to 1.9 kilobases, being favored. We have used the restriction endonucleases HindIII and XbaI singly and together to generate various sized fragments covering the entire HSV-1 genome. These fragments have been bound to cellulose to allow isolation of HSV-1 mRNA annealing to different regions of the viral genome. Discrete sizes of viral mRNA are associated with certain regions of the genome, but the mRNA population hybridizing to even the smallest restriction fragments is complex. We used hybridization of size-fractionated RNA to Southern blots of restriction fragments of HSV-1 DNA generated by the BglII as well as HindIII and XbaI endonucleases to confirm the preparative hybridization data and to provide some overlap data for positioning transcripts. The data of blot and preparative hybridization agreed very well and were combined to construct a preliminary transcription map of HSV-1. Such a map revealed at least two areas of the long unique region of the HSV-1 genome which annealed to a large number of HSV-1 transcripts. Furthermore, discrete-sized mRNA species larger than 5 kilobases in length were found only in the middle of the long unique region. The implications of these data are discussed.